Forming-reduction integrated synthesis method and preparation device of organic liquid hydrogen storage and desorption catalyst

The forming-reduction integrated synthesis method and device address the inefficiencies of conventional catalyst synthesis by integrating granulation and drying/reduction processes, achieving high-yield, cost-effective, and environmentally friendly production of non-precious metal catalysts for organic liquid hydrogen storage.

CN119236944APending Publication Date: 2025-01-03FOSHAN QINGDE HYDROGEN ENERGY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411442184.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Conventional catalyst synthesis methods for organic liquid hydrogen storage and release are cumbersome, leading to long synthesis cycles, catalyst loss, and potential odor emissions, especially when using precious metal catalysts.

Method used

A forming-reduction integrated synthesis method and device that integrates granulation and drying/reduction processes, using non-precious metal catalysts with specific binders and carriers, ensuring minimal human intervention and maintaining catalyst morphology.

Benefits of technology

The method reduces synthesis time and cost, enhances catalyst yield, and maintains catalyst performance comparable to precious metals while minimizing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236944A_ABST
    Figure CN119236944A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogen storage catalysts, in particular to a molding-reduction integrated molding synthesis method and a preparation device of an organic liquid hydrogen storage and desorption catalyst. The preparation method comprises the following steps: 1) mixing an inorganic compound of Ni with a catalyst carrier, then adding a binder, uniformly mixing to prepare a mixture, enabling the mixture to be in a slurry state, and then granulating; 2) after granulation is finished, carrying out extrusion molding to prepare a strip-shaped catalyst precursor material; and 3) drying and reducing the catalyst precursor material in a synthesis chamber to obtain the organic liquid hydrogen storage and desorption catalyst. Molding and reduction of the organic liquid hydrogen storage and desorption catalyst are both achieved in the integrated molding-reduction device, damage to a molded catalyst precursor caused by a large amount of human participation is avoided, the hardness of the finally reduced catalyst reaches the optimal state, meanwhile, the synthesis cost is also saved, and the production efficiency is improved. The synthesized catalyst can be applied to hydrogen absorption and desorption of organic liquid in a large fixed bed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen storage catalysts, and in particular to a molding-reduction integrated molding synthesis method and a preparation device for an organic liquid hydrogen storage and dehydrogenation catalyst. Background Art

[0002] Hydrogen is one of the key components of renewable energy systems. However, the storage and transportation of hydrogen are challenging for the large-scale application of hydrogen energy. Liquid organic hydrogen carrier (LOHC) technology is a possible solution to this problem. With the right organic components, hydrogen can be stored in a chemically bound form, which is safer and has a higher energy density than other solutions. In addition, storage and transportation of high hydrogen-containing LOHC components can be provided under normal ambient conditions.

[0003] In recent decades, researchers have conducted extensive research on different hydrogen carrier pairs and their corresponding catalysts, and have made many important research advances. Among them, methylcyclohexane (MCH) / toluene (TOL), dibenzyl peroxide (H18-DBT) / dibenzyl toluene (H0-DBT), and dodecahydroethylcarbazole (H12-NEC) / N-ethylcarbazole (H0-NEC) three LOHC carrier pairs have been tried for commercialization. For example, Hydrogenious Technologies in Germany uses dibenzyl toluene as the main research object. This dielectric material can achieve a maximum of 57 kg / m 3 The hydrogen storage capacity of Hydrogenious is currently being cooperated with many domestic companies to jointly develop mobile hydrogen storage facilities. Japanese companies such as Chiyoda Chemical and Hrein mainly use toluene / methylcyclohexane as research and development objects, and have achieved integrated development in ocean hydrogen transportation and miniaturization of hydrogenation and dehydrogenation, hydrogenation stations, and distributed energy supply. In my country, Qingde Hydrogen Energy Technology Co., Ltd., Wuhan Hydrogen Energy Co., Ltd., Shaanxi Hydrogen Easy Energy Technology Co., Ltd., Beijing Haiwang Hydrogen Energy Technology Co., Ltd., and Hanrui Hydrogen Energy Technology Group Co., Ltd. have been committed to the industrialization of LOHC technology based on nitrogen heterocyclic compounds. The main organic hydrogen storage carriers are alkyl carbazoles and alkyl indoles.

[0004] However, efficient LOHC hydrogen storage and release requires a suitable catalyst. In order to ensure the normal operation of the LOHC hydrogen storage and release equipment, the catalyst must also have a necessary shape. The conventional catalyst molding method is to first prepare a catalyst precursor, then add an appropriate binder component to the precursor, and then put the evenly mixed catalyst into a granulator for granulation. After the granulation is completed, the catalyst precursor is taken out of the granulator, dried, and then the catalyst precursor is transferred to the synthesis furnace for subsequent synthesis steps. This synthesis method is not only cumbersome and will result in a long synthesis cycle, but will also inevitably cause a loss of catalyst during the precursor transfer process, which will bring huge economic losses, because the catalysts currently used for LOHC hydrogen storage and release are mostly precious metal catalysts. In addition, if the binder selected in the granulation process has a pungent odor, there is also a risk of the odor being emitted into the air during the granulation and precursor transfer process. Summary of the invention

[0005] The embodiments of the present invention provide a forming-reduction integrated synthesis method and preparation device of an organic liquid hydrogen storage and dehydrogenation catalyst. The present invention can improve the yield of the catalyst, save catalyst synthesis time, and reduce the synthesis cost of the catalyst. At the same time, it is a preparation method with high safety and good environmental protection. And the non-precious metal catalyst synthesized by this method also has a catalytic performance that is competitive with that of precious metal catalysts.

[0006] In a first aspect, an embodiment of the present invention provides a forming-reduction integrated synthesis method of an organic liquid hydrogen storage and dehydrogenation catalyst, comprising the following steps: 1) Mixing the inorganic compound of Ni with the catalyst carrier, then adding a binder and mixing them evenly to obtain a mixture, making the mixture in a slurry state, and then granulating; 2) After granulation, extrusion molding is performed to obtain a strip-shaped catalyst precursor material; 3) The catalyst precursor material is dried and reduced in a synthesis chamber to obtain an organic liquid hydrogen storage and dehydrogenation catalyst.

[0007] Preferably, the inorganic compound of Ni in the present invention is one or more selected from nickel chloride, nickel nitrate, nickel hydroxide, and bis(1,5-cyclooctadiene)nickel; The carrier is selected from one or more of nano Al2O3, SiO2 or TiO2; Al2O3, SiO2 and TiO2 have good thermal stability and chemical stability, moderate interaction force with the active components of the catalyst and low cost.

[0008] The binder is selected from one or more of diaspore, PVP, sodium alginate, sodium carboxymethyl cellulose, a mixture of water and ammonia water, and a mixture of water and ethanol.

[0009] Preferably, the content of Ni in the organic liquid hydrogen storage and dehydrogenation catalyst of the present invention is 5% to 50%; within a wide range of Ni content, the catalyst can have a stable morphology and stable performance; The amount of the binder added is 5% to 30% of the mass of the catalyst carrier.

[0010] Preferably, the drying temperature of the present invention is 80°C to 120°C, the drying time is 1h to 3h, and the drying atmosphere is vacuum, Ar or N2; the reduction temperature is 400°C to 600°C, the reduction time is 2h to 4h, the heating rate is 2°C / min to 10°C / min, and the reducing atmosphere is H2 or Ar / H2.

[0011] In the second aspect, an embodiment of the present invention provides an integrated molding-reduction preparation device for an organic liquid hydrogen storage and dehydrogenation catalyst, the device comprising a granulation system, a synthesis system and a control system, the granulation system being arranged at the upper part of the synthesis system and directly communicating with the synthesis system to ensure that the granules are smoothly dropped into the synthesis chamber, the control system being arranged at the lower part of the synthesis system, the granulation system comprising a cover and a granulation chamber, the cover being arranged above the granulation chamber, the cover being provided with a metal cover plate, a sealing ring and a lower metal cover plate from top to bottom, the granulation chamber being provided with an internal cutter, a granulation mold, an external magnetic cutter and a magnet from the inside to the outside, and the granulation mold being replaceable according to granulation requirements.

[0012] Preferably, the synthesis system of the present invention includes a synthesis chamber, which is provided with an air inlet at the top and an air outlet at the diagonal side to allow gas to flow through the synthesis chamber; the bottom and side walls of the synthesis chamber are laid with heating pipes, which can complete the drying and reduction process of the formed particles for synthesis heating.

[0013] More preferably, the synthesis system of the present invention further comprises an observation window, wherein the observation window is sealed to the external threaded rod of the synthesis chamber via a sealing gasket, and the sealing gasket is in an external groove of the synthesis chamber.

[0014] Preferably, the control system of the present invention includes a heating control module, an electric motor control module and a control panel, the heating control module is used to control the heating tube, the electric motor control module includes an electric motor and a connecting rod, the connecting rod is located at the center of the internal cutter and is directly connected to the electric motor, when the electric motor rotates, the connecting rod drives the internal cutter in the granulation system to rotate, and the rear ends of the heating control module and the electric motor control module are connected to the control panel.

[0015] Preferably, the distance between the internal cutter and the granulation mold of the present invention is 0.5-1 mm, the distance between the external magnetic cutter and the granulation mold is 4.5-5.5 mm, and the hole diameter of the granulation mold is 1.5-5 mm.

[0016] Preferably, the material used inside the synthesis chamber of the present invention is high-temperature resistant quartz glass, the middle insulation material is polycrystalline alumina ceramic fiber, and the outermost shell material is stainless steel; the heating temperature of the heating tube is 80-600°C; the observation window is made of high-temperature resistant glass; the electric motor speed is 20rpm-100rpm.

[0017] The technical advantages of the present invention are: (1) The molding and reduction of the organic liquid hydrogen storage and dehydrogenation catalyst of the present invention are both realized in an integrated molding-reduction device, thereby avoiding the damage to the molded catalyst precursor caused by a large amount of human participation, so that the hardness of the finally reduced catalyst reaches the optimal state, and at the same time, the synthesis cost is saved.

[0018] (2) The diaspore, PVP, sodium alginate and sodium carboxymethyl cellulose selected in the present invention are good binders, and their addition amount accounts for 5% to 30% of the mass of the catalyst precursor, which minimizes the influence of the binder on the final catalytic performance. Then, an appropriate amount of water is added to ensure that the mixture of the precursor and the binder is in a semi-solid state. The catalyst precursor in a semi-solid state is easier to shape.

[0019] (3) The present invention uses a granulation mold with a diameter of 1.5 to 5 mm to enable the synthesized catalyst to have an effective barrier effect on the fixed bed filter, so that the catalyst dust of too small a size will not enter other parts of the fixed bed and damage the fixed bed; while too large catalyst particles will cause too many active sites to be buried inside the catalyst particles and cannot be exposed, and effective hydrogenation / dehydrogenation catalytic reaction cannot be carried out.

[0020] (4) The distance between the internal cutter and the granulation mold described in the present invention is 0.5-1 mm, so that the internal cutter can be started with the connecting rod after the electric motor in the control system is turned on. The distance between the external magnetic cutter and the granulation mold is about 5 mm, and the minimum distance between the external magnetic cutter and the granulation mold should be slightly larger than the maximum hole diameter of the granulation mold to ensure that the external magnetic cutter does not damage the morphology of the formed particles. The distance between the external magnetic cutter and the granulation mold cannot be too large, otherwise it will be difficult for the external magnetic cutter to contact the formed strip particles during cutting. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 It is a schematic diagram of a molding-reduction integrated preparation device for an organic liquid hydrogen storage and dehydrogenation catalyst provided in an embodiment of the present invention.

[0023] Figure 2 It is a cross-sectional view of a granulation system of a molding-reduction integrated preparation device for an organic liquid hydrogen storage and dehydrogenation catalyst provided in an embodiment of the present invention.

[0024] Figure 3 This is a morphology diagram of the N1 catalyst prepared by the molding-reduction integrated preparation device for the organic liquid hydrogen storage catalyst provided in Example 1 of the present invention.

[0025] Figure 4 This is a morphology diagram of the N1 catalyst prepared by the organic liquid hydrogen storage catalyst molding-reduction integrated equipment provided in Example 1 of the present invention after a hydrogenation / dehydrogenation cycle.

[0026] Among them, 1-granulation system, 11-lid, 111-upper metal cover plate, 112-sealing ring, 113-lower metal cover plate, 12-granulation chamber, 121-internal cutter, 122-granulation mold, 123-external magnetic cutter, 124-magnet, 2-synthesis system, 21-synthesis chamber, 211-air inlet, 212-air outlet, 213-heating tube, 22-observation window, 221-sealing gasket, 3-control system, 31-heating control module, 32-electric motor control module, 321-electric motor, 322-connecting rod, 33-control panel. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0028] like Figure 1-2 As shown, the molding-reduction integrated preparation device of an organic liquid hydrogen storage and dehydrogenation catalyst of the present invention mainly comprises a granulation system 1, a synthesis system 2 and a control system 3.

[0029] The granulation system 1 comprises a cover 11 and a granulation chamber 12 .

[0030] The cover 11 is located above the granulation chamber 12 and is composed of a metal cover plate 111, a sealing ring 112 and a lower metal cover plate 113 from top to bottom to ensure the airtightness of the granulation chamber 12 during operation.

[0031] The granulation chamber 12 includes an internal cutter 121 , a granulation die 122 and an external magnetic cutter 123 .

[0032] The internal cutter 121 is installed above the granulation mold 122, with a small gap of 0.5 to 1 mm between the two, for cutting the catalyst raw material. The granulation mold 122 can be replaced according to the size of the required catalyst particles to meet different production needs. The external magnetic cutter 123 is used in conjunction with the magnet 124, located outside the granulation mold 122, and maintaining a distance of 4.5 to 5.5 mm between the mold and the internal cutter 121 through magnetic attraction to assist cutting, thereby improving molding efficiency.

[0033] The synthesis system 2 includes a synthesis chamber 21 and an observation window 22 .

[0034] The synthesis chamber 21 includes an air inlet 211 , an air outlet 212 and a heating pipe 213 .

[0035] The air inlet 211 is arranged at the top of the synthesis chamber 21 for introducing necessary gas or steam. The air outlet 212 is located on the diagonal side to ensure that the gas flows evenly in the synthesis chamber and serves as an outlet for the prepared catalyst particles. The heating tube 213 is laid on the bottom and side walls of the synthesis chamber 21. The heating temperature can be adjusted in the range of 80 to 600°C for drying and reducing the catalyst particles. High-temperature resistant quartz glass is used as the internal material of the synthesis chamber 21 and can withstand high temperature environments. Polycrystalline alumina ceramic fiber is used as the middle insulation layer to improve thermal efficiency. The stainless steel shell protects the internal structure and increases overall durability.

[0036] The observation window 22 is made of high temperature resistant glass and is sealed to the external threaded rod of the synthesis chamber 21 through a sealing gasket 221, allowing an operator to monitor the status inside the synthesis chamber in real time.

[0037] The control system 3 includes a heating control module 31 , an electric motor control module 32 and a control panel 33 .

[0038] The heating control module 31 accurately controls the heating temperature of the heating tube 213 to ensure that the catalyst particles are dried and reduced at an appropriate temperature. Electric motor control module 32 Electric motor 321: drives the connecting rod 322 to rotate, and the adjustable speed range is 20rpm to 100rpm. The connecting rod 322 is directly connected to the internal cutter 121, and the rotational power of the electric motor 321 is transmitted to the internal cutter 121 to achieve the cutting and forming of the catalyst raw material. The control panel 33 serves as the operating interface of the entire system, integrating the control functions of the heating control module 31 and the electric motor control module 32, realizing one-button operation and simplifying the operating process. Example 1

[0039] Take 402g of NiCl2·6H2O and 100g of Al2O3, mix them evenly in a mixer, and add water and ammonia water (water and ammonia water are in any ratio) while stirring. When the slurry is stirred to a semi-solid state, transfer the mixed slurry to the granulation chamber 12, wherein the hole of the granulation mold 122 is selected to have a diameter of 5mm, and then seal the upper metal cover sheet 111 and the lower metal cover sheet 113 through the sealing ring 112 and the fixed threaded rod of the granulation chamber 12. Start the rotary motor 321, set the speed to 100 rpm, and the frequency of magnet sliding is 5 min / time. When the magnet 124 slides for the first time, immediately start the heating control of the synthesis chamber 21, set the temperature to 80°C, and at the same time, introduce N2 into the synthesis chamber 21 through the air inlet 211, and the introduced N2 is discharged from the air outlet 212. After the granulation is completed, stop introducing N2 into the synthesis chamber 21, and start introducing Ar / H2 into the synthesis chamber 21. The formed precursor was dried in an Ar / H2 atmosphere for 3 hours. Then the temperature of the synthesis chamber 21 was raised to 600°C at a heating rate of 10°C / min. After the heating was completed, it was kept at 600°C for 4 hours. After the reduction was completed, a Ni / Al2O3 (Ni content of 50%) catalyst was obtained, which was named N1. The catalyst yield was >95%. The morphology after forming is as follows Figure 3 As shown in Figure 2, the morphology after a hydrogenation / dehydrogenation cycle is as follows: Figure 4 As shown. Figure 3 and Figure 4 By comparison, it was found that the structure of the N1 catalyst remained relatively intact before hydrogenation / dehydrogenation compared with that after hydrogenation / dehydrogenation. Example 2

[0040] Take 26 g of Ni(NO3)2·6H2O and 100 g of SiO2, mix them evenly in a mixer, and add water and ethanol (water and ethanol are in any ratio) while stirring. When the slurry is stirred to a semi-solid state, transfer the mixed slurry to the granulation chamber 12, wherein the hole of the granulation mold 122 is selected to have a diameter of 2 mm, and then seal the upper metal cover sheet 111 and the lower metal cover sheet 113 through the sealing ring 112 and the fixed threaded rod of the granulation chamber 12. Start the rotary motor 321, set the speed to 60 rpm, and the frequency of magnet sliding is 8 min / time. When the magnet 124 slides for the first time, immediately start the heating control of the synthesis chamber 21, set the temperature to 100 ° C, and at the same time, introduce Ar into the synthesis chamber 21 through the air inlet 211, and the introduced Ar is discharged from the air outlet 212. After the granulation is completed, stop introducing Ar into the synthesis chamber 21, and start introducing Ar / H2 into the synthesis chamber 21. The formed precursor was dried in an Ar / H2 atmosphere for 2 h. The temperature of the synthesis chamber 21 was then raised to 500°C at a heating rate of 6°C / min. After the heating was completed, it was kept at 500°C for 3 h. After the reduction was completed, a Ni / Al2O3 (Ni content of 5%) catalyst was obtained, which was named N2. The catalyst yield was >95%. Example 3

[0041] Take 52 g of Ni(OH)2 and 100 g of TiO2, mix them evenly in a mixer, add 5 g of diaspore (the binder is 5% of the mass of the carrier TiO2), add water while stirring, and when the slurry is stirred to a semi-solid state, transfer the mixed slurry to the granulation chamber 12, wherein the hole of the granulation mold 122 is selected to have a diameter of 1.5 mm, and then seal the upper metal cover sheet 111 and the lower metal cover sheet 113 through the sealing ring 112 and the fixed threaded rod of the granulation chamber 12. Start the rotary motor 321, set the speed to 20 rpm, and the frequency of magnet sliding is 10 min / time. When the magnet 124 slides for the first time, immediately start the heating control of the synthesis chamber 21, set the temperature to 120°C, and at the same time, introduce Ar into the synthesis chamber 21 through the air inlet 211, and the introduced Ar is discharged from the air outlet 212. After the granulation is completed, stop introducing Ar into the synthesis chamber 21, and start introducing H2 into the synthesis chamber 21. The formed precursor was dried in H2 atmosphere for 1 hour. Then the temperature of the synthesis chamber 21 was raised to 450°C at a heating rate of 2°C / min. After the heating was completed, it was kept at 450°C for 2 hours. After the reduction was completed, a Ni / TiO2 (Ni content was 25%) catalyst was obtained, which was named N3. The catalyst yield was >95%. Example 4

[0042] Take 25g of bis(1,5-cyclooctadiene)nickel and 100g of Al2O3, mix them evenly in a mixer, add 10g of PVP (the binder is 10% of the mass of the carrier Al2O3), add water while stirring, and when the slurry is stirred to a semi-solid state, transfer the mixed slurry to the granulation chamber 12, wherein the hole of the granulation mold 122 is selected to have a diameter of 2mm, and then the upper metal cover sheet 111 and the lower metal cover sheet 113 are sealed through the sealing ring 112 and the granulation chamber 12 fixed threaded rod. Start the rotary motor 321, set the speed to 20 rpm, and the frequency of magnet sliding is 10min / time. When the magnet 124 slides for the first time, the heating control of the synthesis chamber 21 is immediately started, and the temperature is set to 120°C. At the same time, Ar is introduced into the synthesis chamber 21 through the air inlet 211, and the introduced Ar is discharged from the air outlet 212. After the granulation is completed, the introduction of Ar into the synthesis chamber 21 is stopped, and H2 is introduced into the synthesis chamber 21. The formed precursor is dried in the H2 atmosphere for 1 hour. Then the temperature of the synthesis chamber 21 is raised to 450°C at a heating rate of 2°C / min. After the heating is completed, it is kept at 450°C for 2 hours. After the reduction is completed, a Ni / TiO2 (Ni content is 5%) catalyst is obtained, which is named N4. The catalyst yield is >95%. Example 5

[0043] Take 26g of Ni(NO3)2·6H2O and 100g of SiO2, mix them evenly in a mixer, add 20g of sodium alginate (the binder is 20% of the mass of the carrier SiO2), add water while stirring, and when the slurry is stirred to a semi-solid state, transfer the mixed slurry to the granulation chamber 12, wherein the hole of the granulation mold 122 is selected to have a diameter of 2mm, and then seal the upper metal cover sheet 111 and the lower metal cover sheet 113 through the sealing ring 112 and the granulation chamber 12 fixed threaded rod. Start the rotary motor 321, set the speed to 60 rpm, and the frequency of the magnet sliding is 10 min / time. When the magnet 124 slides for the first time, the heating control of the synthesis chamber 21 is immediately started, and the temperature is set to 100°C. At the same time, Ar is introduced into the synthesis chamber 21 through the air inlet 211, and the introduced Ar is discharged from the air outlet 212. After granulation, the introduction of Ar into the synthesis chamber 21 was stopped, and Ar / H2 was introduced into the synthesis chamber 21. The formed precursor was dried for 2 hours in an Ar / H2 atmosphere. Then the temperature of the synthesis chamber 21 was raised to 500°C at a heating rate of 10°C / min. After the heating was completed, it was kept at 500°C for 2 hours. After the reduction was completed, a Ni / Al2O3 (Ni content of 5%) catalyst was obtained, which was named N5. The catalyst yield was >95%. Example 6

[0044] Take 26g of Ni(NO3)2·6H2O and 100g of SiO2, mix them evenly in a mixer, add 30g of sodium carboxymethyl cellulose (the binder is 30% of the mass of the carrier SiO2), add water while stirring, and when the slurry is stirred to a semi-solid state, transfer the mixed slurry to the granulation chamber 12, wherein the hole of the granulation mold 122 is selected to have a diameter of 2mm, and then seal the upper metal cover sheet 111 and the lower metal cover sheet 113 through the sealing ring 112 and the granulation chamber 12 fixed threaded rod. Start the rotary motor 321, set the speed to 60 rpm, and the frequency of the magnet sliding is 10 min / time. When the magnet 124 slides for the first time, the heating control of the synthesis chamber 21 is immediately started, and the temperature is set to 100°C. At the same time, Ar is introduced into the synthesis chamber 21 through the air inlet 211, and the introduced Ar is discharged from the air outlet 212. After granulation, stop passing Ar into the synthesis chamber 21, and start passing Ar / H2 into the synthesis chamber 21. The formed precursor is dried for 2 hours in an Ar / H2 atmosphere. Then the temperature of the synthesis chamber 21 is raised to 500°C at a heating rate of 10°C / min. After the heating is completed, it is kept at 500°C for 2 hours. After the reduction is completed, a Ni / Al2O3 (Ni content is 5%) catalyst is obtained, which is named N6. The catalyst yield is >95%.

[0045] Comparative Example 1

[0046] A comparative experiment was conducted using a JZL-90 laboratory extrusion granulator. Take 402g of NiCl2·6H2O and 100g of Al2O3, mix them evenly in a mixer, and add water and ammonia water (water and ammonia water are in any ratio) while stirring. When the slurry is stirred to a semi-solid state, the mixed slurry is transferred to a granulator, where the hole of the granulation mold is selected to have a diameter of 5mm, and the bottom of the granulation mold is used to hold the already made granules with a tray. Then start the granulator, set the speed to 100 rpm, and manually scrape the already made granules from the granulation mold once every 5 minutes. After the granulation is completed, the made granules are placed in an oven and dried at 80°C for 6 hours. Then the dried catalyst precursor is transferred to a reduction furnace and reduced at 600°C for 4 hours, where the heating rate is set to 10°C / min. After the reduction, a Ni / Al2O3 (Ni content is 50%) catalyst is obtained, which is named DN1. The entire synthesis process takes at least about 4 hours longer than that of Comparative Example 1 (the drying process takes 3 hours longer, and the frequent transfer of the precursor takes at least 1 hour), and the catalyst yield is only 75%, and additional labor costs are required. It should be noted here that since the drying procedure was started during the granulation process in Comparative Example 1, the time was greatly shortened during the drying process after the granulation. The JZL-90 laboratory extrusion granulator does not have the function of drying while granulating. The catalyst yield is greatly reduced compared to Comparative Example 1 because 1) the frequent transfer of the precursor during the granulation reduction process inevitably causes the loss of the catalyst; 2) the particles will splash outside the tray during the granulation process.

[0047] Comparative Example 2

[0048] The JZL-90 laboratory extrusion granulator was used for comparative experiments. A small heating table was added under the tray under the mold. 402 g of NiCl2·6H2O and 100 g of Al2O3 were mixed evenly in the mixer, and water and ammonia water (water and ammonia water were in any ratio) were added while stirring. When the slurry was stirred to a semi-solid state, the mixed slurry was transferred to the granulator, in which the hole of the granulation mold was selected to have a diameter of 5 mm, and the bottom of the granulation mold was used to hold the prepared granules with a tray. Then the granulator was started, the speed was set to 100 rpm, and the prepared granules were manually scraped off from the granulation mold every 5 minutes. After the granulation was completed, the prepared granules were placed in an oven and dried at 80°C for 4.5 hours. Then the dried catalyst precursor was transferred to the reduction furnace and reduced at 600°C for 4 hours, with the heating rate set to 10°C / min. After the reduction, the Ni / Al2O3 (Ni content was 50%) catalyst was obtained, which was named DN2. The entire synthesis process takes at least about 2 hours longer than that of Comparative Example 1, and the catalyst yield is about 70%, and additional labor costs are required. The drying time of Comparative Example 2 is still longer than that of Comparative Example 1, because there is flowing gas purge during the granulation and drying process of Comparative Example 1, which greatly increases the drying rate of the N1 catalyst.

[0049] Comparative Example 3

[0050] The JZL-90 laboratory extrusion granulator was used for comparative experiments. A stainless steel sieve with a hole diameter of 1~2mm was placed under the mold, and a small air drier was placed at the bottom of the sieve. 402g of NiCl2·6H2O and 100g of Al2O3 were mixed evenly in the mixer, and water and ammonia water (water and ammonia water were in any ratio) were added while stirring. When the slurry was stirred to a semi-solid state, the mixed slurry was transferred to the granulator, in which the hole of the granulation mold was selected to have a diameter of 5mm. Then the granulator was started, the speed was set to 100 rpm, and the granules were manually scraped off from the granulation mold every 5 minutes. After the granulation was completed, the granules were placed in an oven and dried at 80℃ for 3h. Then the dried catalyst precursor was transferred to the reduction furnace and reduced at 600℃ for 4h, with the heating rate set to 10℃ / min. After the reduction, the Ni / Al2O3 (Ni content was 50%) catalyst was obtained, which was named DN3. The whole synthesis process takes at least about 1 hour more time than Comparative Example 1, and the catalyst yield is about 67%, and more additional labor costs are required. In this comparative example, although the addition of the air drier greatly improves the drying time of the DN3 catalyst to make it consistent with the drying time of Example 1, the air drier will inevitably blow a part of the catalyst out of the screen when it is working, causing the catalyst yield to decrease. And since the granulation scheme of Comparative Example 3 requires manual scraping of the prepared granules from the granulation mold every 5 minutes, there is no way to use a cover to cover the entire granulation system to avoid the prepared granules being blown away.

[0051] The performance of the organic liquid hydrogen storage and dehydrogenation catalysts obtained in the examples and comparative examples is tested below. The test results are shown in Table 1.

[0052] 100g of the organic liquid hydrogen storage and dehydrogenation catalysts (catalysts N1, N2, N3, N4, N5, N6, DN1, DN2, DN3) obtained in Examples 1 to 6 and Comparative Examples 1 to 3 and 200g of N-ethylcarbazole were placed in a fixed bed, and N-ethylcarbazole was intermittently hydrogenated at 8 MPa and 150°C. After the hydrogenation, 12H-N-ethylcarbazole was dehydrogenated at a temperature of 200°C.

[0053] Table 1 Comparison of the hydrogenation effects of the catalysts prepared in the examples and comparative examples on N-ethylcarbazole

[0054] *The theoretical hydrogenation conversion rate of N-ethylcarbazole is 5.7%.

[0055] Table 2 Comparison of the hydrogen release effects of the catalysts prepared in the examples and comparative examples on 12H-ethylcarbazole

[0056] As can be seen from Table 1, the selectivity of the fully hydrogenated product 12H-NEC of the catalysts of Examples 1 to 6 after 5 h of hydrogenation reaction is more than 90%, and even the N4 catalyst can reach 99%. The catalysts of Comparative Examples 1 to 3 can only reach 80% at most. This is because the N1~N6 catalysts have a higher hardness than the DN1~DN3 catalysts, and the high hardness makes it easier for the N1~N6 catalysts to maintain their morphology during hydrogenation / dehydrogenation. The stable catalyst morphology means the exposure of stable catalyst active sites, which ensures the hydrogenation / dehydrogenation stability of the N1~N6 catalysts. The high hardness of the N1~N6 catalysts comes from the fact that there is little human participation in the catalyst precursor during the molding-reduction process, which guarantees the stability of the precursor molding morphology to the greatest extent, which lays the foundation for the high hardness of the reduced catalyst. The DN1~DN3 catalyst precursors are frequently transferred during the molding process, and the precursors at this time are still in a semi-solid state, and the morphology is easily destroyed, which further makes the reduced catalysts extremely easy to pulverize. This makes the morphology of the DN1~DN3 catalysts more likely to collapse when working in a fixed bed. This situation is more prominent during the hydrogen release process. In particular, the D3 catalyst was severely powdered after 2 hours of hydrogenation, so the experiment was immediately terminated for safety reasons.

Claims

1. A molding-reduction integrated synthesis method of an organic liquid hydrogen storage catalyst, characterized in that: The following steps are involved: 1) Mixing the inorganic compound of Ni with the catalyst carrier, then adding a binder and mixing them evenly to obtain a mixture, making the mixture in a slurry state, and then granulating; 2) After granulation, extrusion molding is performed to obtain a strip-shaped catalyst precursor material; 3) The catalyst precursor material is dried and reduced in a synthesis chamber to obtain an organic liquid hydrogen storage and dehydrogenation catalyst.

2. The synthesis method according to claim 1, characterized in that: The inorganic compound of Ni is selected from one or more of nickel chloride, nickel nitrate, nickel hydroxide, and bis(1,5-cyclooctadiene)nickel; The carrier is selected from one or more of nano-Al2O3, SiO2 or TiO2; The binder is selected from one or more of diaspore, PVP, sodium alginate, sodium carboxymethyl cellulose, a mixture of water and ammonia water, and a mixture of water and ethanol.

3. The synthesis method according to claim 1, characterized in that: The content of Ni in the organic liquid hydrogen storage and dehydrogenation catalyst is 5% to 50%; when the binder is a mixture of water and ammonia or a mixture of water and ethanol, the added amount is any amount; when the binder is diaspore, PVP, sodium alginate or sodium carboxymethyl cellulose, the added amount is 5% to 30% of the mass of the catalyst carrier.

4. The synthesis method according to claim 1, characterized in that: The drying temperature is 80°C to 120°C, the drying time is 1h to 3h, and the drying atmosphere is vacuum, Ar or N2; the reduction temperature is 400°C to 600°C, the reduction time is 2h to 4h, the heating rate is 2°C / min to 10°C / min, and the reduction atmosphere is H2 or Ar / H2.

5. A molding-reduction integrated preparation device for an organic liquid hydrogen storage and dehydrogenation catalyst, used for preparing the organic liquid hydrogen storage and dehydrogenation catalyst according to claim 1, characterized in that: The preparation device comprises a granulation system (1), a synthesis system (2) and a control system (3), wherein the granulation system (1) is arranged on the upper part of the synthesis system (2) and is directly connected to the synthesis system (2), and the control system (3) is arranged on the lower part of the synthesis system (2). The granulation system (1) comprises a cover (11) and a granulation chamber (12), wherein the cover (11) is arranged above the granulation chamber (12), and the cover (11) is provided with a metal cover sheet (111), a sealing ring (112) and a lower metal cover sheet (113) from top to bottom, respectively; and the granulation chamber (12) is provided with an internal cutter (121), a granulation mold (122), an external magnetic cutter (123) and a magnet (124) from inside to outside, respectively; and the granulation mold (122) can be replaced according to granulation requirements.

6. The molding-reduction integrated preparation device of the organic liquid hydrogen storage and dehydrogenation catalyst according to claim 5, characterized in that: The synthesis system (2) comprises a synthesis chamber (21), an air inlet (211) is arranged at the top of the synthesis chamber (21), an air outlet (212) is arranged at the diagonal side, and heating pipes (213) are laid at the bottom and side walls of the synthesis chamber (21).

7. The molding-reduction integrated preparation device of the organic liquid hydrogen storage and dehydrogenation catalyst according to claim 6, characterized in that: The synthesis system (2) further comprises an observation window (22), wherein the observation window (22) is sealed with an external threaded rod of the synthesis chamber (21) via a sealing gasket (221), wherein the sealing gasket (221) is in an external groove of the synthesis chamber (21).

8. The molding-reduction integrated preparation device of the organic liquid hydrogen storage and dehydrogenation catalyst according to claim 7, characterized in that: The control system (3) comprises a heating control module (31), an electric motor control module (32) and a control panel (33); the heating control module (31) is used to control the heating tube (213); the electric motor control module (32) comprises an electric motor (321) and a connecting rod (322); the connecting rod (322) is located at the center of the internal cutter (121) and is directly connected to the electric motor (321); when the electric motor (321) rotates, the connecting rod (322) drives the internal cutter (121) in the granulation system to rotate; the rear ends of the heating control module (31) and the electric motor control module (32) are connected to the control panel (33).

9. The molding-reduction integrated preparation device of the organic liquid hydrogen storage and dehydrogenation catalyst according to claim 8, characterized in that: The distance between the internal cutting knife (121) and the granulation die (122) is 0.5-1 mm, and the distance between the external magnetic cutting knife (123) and the granulation die (122) is 4.5-5.5 mm.

10. The molding-reduction integrated preparation device of the organic liquid hydrogen storage and dehydrogenation catalyst according to claim 8, characterized in that: The material used inside the synthesis chamber (21) is high-temperature resistant quartz glass, the insulation material in the middle is polycrystalline alumina ceramic fiber, and the outermost shell material is stainless steel; the heating temperature of the heating tube (213) is 80 to 600° C.; the observation window (22) is made of high-temperature resistant glass; and the rotation speed of the electric motor (321) is 20 rpm to 100 rpm.